Application of Fala Kancing House Construction as a Simple Earthquake Resistant House Concept Today - Marasabessy, Firdawaty; Muhammad, Asri A.; Andriani, Tiara Puput (Universitas Khairun, 2025)
One of the traditional houses that can withstand earthquake shocks is the Fala Kancing. Fala Kancing is a local name that means a house that has interlocking construction. This research aims to analyze and develop the Fala Kancing house as a simple earthquake-resistant and environmentally friendly house model based on contemporary local wisdom. This research uses a descriptive-qualitative approach with analysis techniques using thematic approaches for qualitative aspects, and comparative analysis of house morphology for spatial and structural aspects. The research results provide recommendations for a prototype of an earthquake-resistant fala kancing house (new type) by maintaining the concept of button construction with the main material being wood. The interlocking space frame construction between column and beam foundations can be used as the main structure of a simple earthquake-resistant house. The size of the plan with the front side of the house is smaller than the side of the house, the space configuration facilitates the evacuation process, and still maintains the wall material from ancak bamboo and kalero but with a model that is adjusted for ease in the process of installing wall materials.